Building Students' Communication Skills in Learning English through Lesson Study at Senior High School - Mahmud, Adi F.; Umahuk, Sabariah; Fudji, Sri Rahayu; Noh, Sofia A.; Soleman, Ferawati; Gafar, Amin (Universitas Pendidikan Mandalika, 2023)
One of the 21st century learning skills needed is communication skills. Communication skills have crucial roles to help students in facing global competitive and digital era nowadays. However, most of learnings at the middle and senior high schools ignore it but teachers still apply conventional learning methods to achieve it. Due to the problems, this study aims to build students' communication skills, and to find out the implementation of lesson study on students’ communication skills in learning English at senior high school through lesson study. It is a descriptive qualitative study conducted at Senior High School of 10 Kota Ternate. 100 students were selected through purposive sampling as the research samples. Data were collected by applying lesson study activities in 4 cycles through direct observation in learning process using communication skills instruments developed by the Ministry of Education and Culture. Communication skill indicators focus on 6 indicators. Data were analysed using a Likert scale of 5-1. Based on the result of analysis, the study showed that students’ communication skills are improved and developed gradually. In addition, lesson study has given a positive impact toward students ‘communication skills in learning English. It was proven that students’ communication skill develops significantly and linearly from cycle I (43.33) into cycle II (63, 33). Thus, the students’ communicative skills were improved as well from cycle III (76, 66) into cycle IV (93,33). Therefore, this study can be concluded lesson study activities in learning English are alternative solution to build students' communication skills, learning English through the implementation of lesson study has a positive impact on the development of communication skills, and students' communication skills through lesson study develop gradually and linearly and convey significant development.